Adsorbate-induced structural changes in 1-3 nm platinum nanoparticles - Lei, Yu; Zhao, Haiyan; Rivas, Rosa Diaz; Lee, Sungsik; Liu, Bin; Lu, Junling; Stach, Eric; Winans, Randall E.; Chapman, Karena W.; Greeley, Jeffrey P.; Miller, Jeffrey T.; Chupas, Peter J.; et al. (My University, 2014)
We investigated changes in the Pt–Pt bond distance, particle size, crystallinity, and coordination of Pt nanoparticles as a function of particle size (1–3 nm) and adsorbate (H2, CO) using synchrotron radiation pair distribution function (PDF) and X-ray absorption spectroscopy (XAS) measurements. The ∼1 nm Pt nanoparticles showed a Pt–Pt bond distance contraction of ∼1.4%. The adsorption of H2 and CO at room temperature relaxed the Pt–Pt bond distance contraction to a value close to that of bulk fcc Pt. The adsorption of H2 improved the crystallinity of the small Pt nanoparticles. However, CO adsorption generated a more disordered fcc structure for the 1–3 nm Pt nanoparticles compared to the H2 adsorption Pt nanoparticles. In situ XANES measurements revealed that this disorder results from the electron back-donation of the Pt nanoparticles to CO, leading to a higher degree of rehybridization of the metal orbitals in the Pt-adsorbate system.
Keywords: Platinum nanoparticles; Heterogeneous catalyst; X‐ray absorption spectroscopy; Pair distribution function; Bond distance; Contraction; Ligands